Financial Performance and Regional Original Income on Provincial Capital Expenditures in Indonesia - Angga Yudha Pradana; Kartika Hendra Ts; Istiatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of financial performance and local revenue on capital expenditure of provinces in Indonesia. Financial performance is proxied by the degree of fiscal decentralized ratio, dependency ratio, and efficiency ratio. This type of research is quantitative research. The study was conducted in provinces in Indonesia using secondary data in the form of data on the Regional Revenue and Expenditure Budget realization data from 2020 to 2022. The data analysis technique used multiple regression, which was used to test the four hypotheses. The results of this study provide empirical evidence that dependency ratio, efficiency ratio, and local revenue have an effect on capital expenditure, while the degree of fiscal decentralized ratio has no effect on capital expenditure. However, the contribution of the influence of all these independent variables on capital expenditure as the dependent variable is 81.9%, while 18.1% is influenced by other variables not examined in this study.